Transit Index of Subdivision Graphs - Reshmi, K. M.; Pilakkat, Raji (Communications in Mathematics and Applications, 2021)
The concept of transit of a vertex and transit index of a graph was defined by the authors in their previous work. The transit of a vertex v is "the sum of the lengths of all shortest path with v as an internal vertex” and the transit index of a graph \(G\) is the sum of the transit of all the vertices of it. In this paper, we investigate transit index of sub-division graphs.